HUBUNGAN PERILAKU TENTANG KESEHATAN GIGI DAN MULUT DENGAN KEJADIAN KARIES GIGI ANAK DI SD CINTA RAKYAT 4 KELAS IV DAN V - Irma Nurianti; Artha Dewi Magdalena Bako (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2018)
Cases of tooth decay in children are still needed and children whose teeth are damaged and rotten because they like sweet foods are common in our society. Many parents do not need to do dental treatment because the teeth will change with permanent teeth after a large child. Unhealthy teeth will affect the process and processing of food. Early dental care has been done to avoid other dental problems: cavities, kropos, and swelling of the gums. This research used cross sectional approach method. The research was done at SD Cinta Rakyat 4 Pematangsiantar. The sample in this study were 94 people. The variables that have relationship with dental caries incidence are knowledge variable p = 0,008, attitude p = 0,037 and from multivariate test variable which has the most dominant relationship is knowledge variable with p value = 0,046 Exp value (B) = 16.230. Suggestion given The need for counseling and socialization to the school and parents especially on school children about the importance of oral health since early and expected the school participate actively participate by cooperating cross program and cross sector to support effort of dental caries prevention in child.